Methodological Principles of Implementation of International Health Regulations (2005) in the Territory of the Russian Federation - G. G. Onischenko (Проблемы особо опасных инфекций, 2010)
Implementation of IHR (2005) in the territory of Russian Federation is beyond the scope of formal admission and technical execution. Fundamentally amended and principally new conceptual essentials of the present international document in relation to previously valid IHR (1969) are to be implemented. In view of above-mentioned, the realization of IHR (2005) is of experimental (research) character to a certain extent. In connection with this, the procedure of functioning of IHR (2005) demands the monitoring and permanent evaluation by the WHO (in the reports of Director-General) with regards to correspondence of the document to the modern epidemiological, social and economic, and geopolitical realities. The IHR (2005) realization in the territory of the Russian Federation demands the development of a certain methodology and special algorithm of activity which include the differentiation of a range of components of conceptual originality of this document, their integration into the content, principles of sanitary protection, improvement of its 3-levels system on the basis of structural and functional strengthening of the network for monitoring of infectious and parasitic diseases agents, training of specialists on IHR (2005) and sanitary protection of the Russian Federation territory.